A solution-route processed multicomponent Cu2ZnSn (S1-x Sex)4 nanocrystals: A potential low-cost photocatalyst. (10th September 2022) - Semalti, Pooja; Sharma, Vikash; Sharma, Shailesh Narain
Abstract: An exemplary perspective to comprehend the underlying role of multicomponent nanocrystals such as CZTS/SSe/Se (Cu2 ZnSnS4 /(SSe)4 /Se4 ) revives the thrust for pioneering the non-vacuum approach for the development of multi-component-based chalcogenides utilizing organic solvents for the formation of nanocrystals, ideal for photo-voltaic/catalysts. This article envisages the employment of Trioctylphosphine (TOP) and Trioctylphosphine Oxide (TOPO) as capping agents cum solvent for CZTS/SSe/Se; the work proceeds with the anionic ratio variations in pristine counterparts of CZTSSe, i.e., to speculate the potential of quaternary chalcogenides where the properties of different materials coalesce and able to improve the characteristics efficiently. Gradually changing the ratio during nanocrystal synthesis via a high-temperature colloidal route imposes precise control over the properties. The synthesized nanocrystals are ingrained in Se-rich and highly crystalline, inhibiting the exigency of selenization and high-temperature annealing. Electrochemical, optical, and structural analysis was intensively studied and the best aliquot Se-ratio was considered to proceed as a photocatalyst. Photocatalysis is an enunciating approach for first aiding wastewater consisting of toxic materials, especially dyes and textile effluents, under sunlight. While, the converging lens deployment uplifts the efficiency and rate of reaction by many folds, it pioneers a new route of energy applications commercially. Graphical abstract: Novelty Production in each stage produces hazardous by-products which mainly cause pollution, especially water pollution, raises concern to agriculture and the whole ecosystem and its continuous release is a serious threat to nature. Present work highlights the degradation of hazardous water pollutants, which is very relevant to the scope of the journal. Present work on CZTS1-x Sex nanoparticles synthesized by hot-injection technique for efficient photodegradation in visible light. Hydrophilic CZTS1-x Sex was utilized for photodegradation of organic and textile pollutants using the converging lens, which enhances the catalytic efficiency and rates constant. Efficiency ∼99% & Rate constant ∼0.3 min −1 reported without noble metal co-catalyst. Image 1 Highlights: Rapid colloidal route synthesis of Multicomponent CZT (S1-x Sex )4 based catalysts. Se:S ratios were studied for CZTS1-x Sex & examined for the best characteristics. Photocatalytic degradation of hazardous pollutants done by optimized hydrophilic CZTSSe. A converging lens was used to study photodegradation. Efficiency ∼99% & Rate constant ∼0.3 min −1 reported without noble metal co-catalyst.